Differential Contribution of Oxidative and Glycolytic Energy to Thrombin-Induced Platelet Functions - Kobayashi, Bonro; Watanabe, Yasuko; Takasugi, Naoyuki; Kurita, Makiko (Thrombosis and Haemostasis, 1979)
When washed rabbit-blood platelets were preincubated in an artificial medium in the absence of external substrates, they aggregated in response to a low concentration of thrombin. The aggregation was completely inhibited after the preincubation with respiratory inhibitors. When glucose together with the respiratory inhibitors was added during the incubation, the aggregation was accelerated, whilst it was counteracted when Krebs-cycle substrates were added.ATP was generated actively during the incubation in the absence of external substrates, as well as in the presence of succinate. The ATP-generation was extremely inhibited by oligomycin. When glucose was added during the incubation with the respiratory inhibitor, the comparable amount of ATP with those in the oxidative systems was generated. Metabolic ADP was accumulated in the oxidative systems, particularly in the presence of succinate, in contrast to its low level in the glucose + oligomycin system. The results suggest that the counteraction of the aggregation by the Krebs-cycle substrate is attributed to the low adenylate energy charge. It is suggested that anaerobic glycolysis creates favorable energy condition for aggregation as compared with oxidative phosphorylation, although the washed platelets can be energized to a level above threshold of the aggregation when either one of the two energy generating systems is exerted.After the incubation of the platelets in the presence of thrombin, a higher level of metabolic ATP was observed under glycolytic condition, than under oxidative condition. Pulse-labelling experiments showed that ADP produced during the aggregation was rephosphorylated in a later part of the incubation in the glucose + KCN-fortified system. In the succinate-fortified system, the re-phosphorylation was very slow. The results suggest that oxidative phosphorylation is reduced in platelet aggregates treated with thrombin.